Limiting factors for snail’s pace success of immunization - Arunachalmath, Pavitra V.; Murteli, Vijayakumar B. (International Journal of Contemporary Pediatrics, 2021)
Background: The practice of immunization dates back to hundreds of years. Buddhist monks drank snake venom to confer the immunity against snake bite. World Health Organization (WHO) covers broad scope of global activities in order make the globe free of vaccine preventable diseases. Many surveillance activities are going on, in order to fulfill the aim of disease free globe. Methods: Children admitted to the Pediatric ward of Belgavi Institute of Medical Sciences were enrolled and parents/ guardians were enquired about the vaccination the child received and their knowledge about immunization and interpretation was done to find out the reasons for snail’s pace of successful elimination of the vaccine preventable diseases. Results: Out of 630 participants, 364 had partial immunization and 12 (1.9%) were un- immunized. Poor knowledge being the first reason found in 247 (67.9%) children. No visit by the health worker was the 2nd reason found in 220 (60.4%) children and child illness was the third reason in 116 (31.9%) children. Conclusions: In order to increase the rates of immunization in the community, improving the knowledge of community, about the benefits of immunizing their children as well as empowering the grass root health workers in immunizing the children of their locality can help us achieve a nation free of vaccine preventable diseases.